A utilização de estratégias de ensino e de avaliação na formação de engenheiros: um estudo de métodos mistos - Luz, Samoara Viacelli da (2018)
The objective of the study was to analyze how teaching and assessment strategies are used by teachers of the Federal University of Technology – Paraná in training of engineers. The main factors that justify this study are the small number of studies dealing with pedagogical issues in engineering education, the current context of values that require a multiplicity of functions of the engineer and the training process under the influence of teaching and evaluation strategies. The study is based on concepts developed by several authors of the areas of engineering education and higher education didactics who discuss the history, problems, the need for changes in this area and strategies of teaching and evaluation in this level of education. The methodological approach adopted was the explanatory sequential mixed method design, composed of a quantitative phase followed by a qualitative phase that helps to understand in more depth the quantitative results obtained in the first phase. The study was conducted in three Campi of the Federal University of Technology - Paraná. The research responsibles were teachers who taught specific and / or vocational disciplines in 11 engineering courses. In the first phase of the quantitative study, a questionnaire was developed to collect data. The instrument was validated by a panel of experts, tested in a pilot study and administered to a sample of 199 teachers. Data were submitted to descriptive statistics and non-parametric statistics. The results indicated the frequency of use of teaching and evaluation strategies; the adoption of behaviors related to the teaching-learning process; the importance that teachers attribute to various aspects related to the acquisition of didactic-pedagogical skills; and the influence of some personal and contextual characteristics on the definition of teaching strategies and evaluation used. Based on the quantitative results, a semi-structured interview protocol was administered to 17 teachers. The answers of the teachers allowed a deepening of the results obtained in the quantitative phase. The set of results showed that most teachers do not know and / or do not use teaching strategies suggested by the active learning and formative evaluation proposals, but that, in the meantime, in the development of the classes, they seek to promote an active participation of the students in the discussions about content taught, develop and evaluate superior aspects to the ability of memorizing and reproducing; that the process of teaching and evaluation developed, they are focused on the teacher; that the main factors that influence the definition of teaching and assessment strategies used are characteristics that are directly related to didactic practice; and that the acquisition of didactic-pedagogical abilities still works mainly through the everyday classroom experience. This research contributed to a broader understanding of didactic practice in engineering courses, but it is evident that more studies are needed to identify other specificities of higher education.